Physicochemical and Biological Properties of Fibrous Pseudomonas Bacteriophages - Minamishima, Y. (1968)
Two fibrous Pseudomonas phages, Pf1 and Pf2, have been isolated and characterized. The phages were serologically related and were indistinguishable morphologically when viewed by electron microscopy. Both phages formed minute turbid plaques. A simple method was devised for easy differentiation of such plaques from the bacterial lawn. The infected bacteria continued to grow and to liberate the phages into the medium. The phages were collected from the turbid “lysate” by salting out and were purified by differential centrifugation and density gradient centrifugation. The purified phages were sensitive to ultrasonics and to a proteolytic enzyme, Nagarse. A rapid lysis mutant was obtained from the progeny of plaquepurified Pf2. Pf2 was spontaneously produced by strain P28 of P. aeruginosa. Neither acridine orange nor antiserum affected the phage-producing capacity of the bacteria.